Microspectroscopy (μFTIR) reveals co-localization of lipid oxidation and amyloid plaques in human Alzheimer disease brains - Benseny-Cases, Núria; Klementieva, Oxana; Cotte, Marine; Ferrer, Isidre; Cladera, Josep (Analytical chemistry (Washington), 2014)
Amyloid peptides are the main component of one of the characteristic pathological hallmarks of Alzheimer's disease (AD): senile plaques. According to the amyloid cascade hypothesis, amyloid peptides may play a central role in the sequence of events that leads to neurodegeneration. However, there are other factors, such as oxidative stress, that may be crucial for the development of the disease. In the present paper, we show that it is possible, by using Fourier tranform infrared (FTIR) microscopy, to co-localize amyloid deposits and lipid peroxidation in tissue slides from patients affected by Alzheimer's disease. Plaques and lipids can be analyzed in the same sample, making use of the characteristic infrared bands for peptide aggregation and lipid oxidation. The results show that, in samples from patients diagnosed with AD, the plaques and their immediate surroundings are always characterized by the presence of oxidized lipids. As for samples from non-AD individuals, those without amyloid plaques show a lower level of lipid oxidation than AD individuals. However, it is known that plaques can be detected in the brains of some non-AD individuals. Our results show that, in such cases, the lipid in the plaques and their surroundings display oxidation levels that are similar to those of tissues with no plaques. These results point to lipid oxidation as a possible key factor in the path that goes from showing the typical neurophatological hallmarks to suffering from dementia. In this process, the oxidative power of the amyloid peptide, possibly in the form of nonfibrillar aggregates, could play a central role.